1997
DOI: 10.1021/jp971733h
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Molecular Mechanics−Valence Bond Method:  Photophysics of Styrene and Indene

Abstract: We have recently studied the excited states of the simplest aryl olefin styrene (Bearpark, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…[25] Moreover, high level computational studies have simulated the potential energy curve of the excited state looking for conical intersections between S 1 and S 0 to account for the non-radiative processes of indene. [26] They found that the main mechanism involved is a fast and efficient internal conversion process. Therefore, the linkage of indene to BODIPY, via a vinyl group, results in a negative effect on the fluorescence capacity of the BODIPY chromophore, owing, probably, to the internal conversion of the indene group.…”
Section: Fluorene-bodipy Derivativesmentioning
confidence: 99%
“…[25] Moreover, high level computational studies have simulated the potential energy curve of the excited state looking for conical intersections between S 1 and S 0 to account for the non-radiative processes of indene. [26] They found that the main mechanism involved is a fast and efficient internal conversion process. Therefore, the linkage of indene to BODIPY, via a vinyl group, results in a negative effect on the fluorescence capacity of the BODIPY chromophore, owing, probably, to the internal conversion of the indene group.…”
Section: Fluorene-bodipy Derivativesmentioning
confidence: 99%
“…1 Over many years, we have been able to understand the structures of model conical intersections using these methods. [54][55][56][57][58] In general, VB methods use a wavefunction that is a product of spin-coupled pairs defined in Eqn (3.1). [51][52][53] A full analysis of the cases of 3 electrons with 3 orbitals and 4 electrons with 4 orbitals has been given by Vanni et al 3 The 6 orbitals with 6 electrons problem has been analyzed by Blancafort et al 4 As we have discussed, we shall begin with situations where the wavefunction is dominated by "covalent" configurations, and the "ionic" configurations play no role.…”
Section: Introduction To Qualitative Vb Theorymentioning
confidence: 99%
“…However, the natural orbital occupations at the CAS12 D2h structures (given in table 1) suggest that a correct zero-order description of So and S1 in D2h symmetry can be obtained by using an active space smaller than the full 12n orbital set. The smallest space which could describe both states simul- In a recent study, MMVB and CASSCF results were compared for the ground and valence excited states of styrene [41]. For planar structures, the relative energies were found to be within f 1 0 % of each other, and the ordering of states was the same.…”
Section: Methodsmentioning
confidence: 99%